Tribocorrosion and electrochemical behaviour of nanocrystalline diamond coated Ti based alloys for orthopaedic application. (February 2017) - Gopal, Vasanth; Chandran, Maneesh; Rao, M.S. Ramachandra; Mischler, Stefano; Cao, Shoufan; Manivasagam, Geetha
Abstract: Metallic implants such as hip and knee often fail due to the combined action of wear and corrosion. Nanocrystalline diamond (NCD) coatings on metallic implants can be a potential candidate to overcome this issue. In this work, we investigated the tribocorrosion and electrochemical behaviour of Nanocrystalline Diamond (NCD) Coatings deposited on Cp-Ti, Ti-6Al-4V and Ti-13Nb-13Zr using hot filament chemical vapour deposition (HFCVD) technique. The results demonstrate that the factors such as intercrystallite pores, TiC interlayer, and electrical conductivity influenced the electrochemical behaviour of all the NCD coatings. Under tribocorrosion, an unexplainable shift in the open circuit potential (OCP) was noticed at the initiation of sliding. Further, a continuous decrease in OCP was also observed as the sliding progress. Highlights: Intercrystallite pores in the NCD coatings induce crevice corrosion of Ti alloys. At the onset of sliding, minimal potential drop and a sudden increase was observed. Corrosion of NCD coatings was predominant during sliding.